Visiting measures and an ergodic theorem for a sequence of iterations with random perturbations - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
By using local visiting measures, we describe the limit behavior of a sequence of iterations with random unequally distributed perturbations. As a corollary, we obtain a version of the local ergodic theorem.